Learner’s Mental Model and the need for the Creative Teacher - MEGA, AFAF (University of El-oued, 2016)
Abstract: This paper endeavors to shed light on the learner’s mental model, its importance in understanding the learner’s mental representation regarding his learning experience. Sometimes, the wrong mental model might lead to wrong interpretations and wrong future decisions which might hinder the learning situation as a whole. Therefore, the presence of the creative teacher to deal with the learner’s mental model is crucial as he inquires and seeks for alternatives to solve the learning problems. On the light of this, our paper is divided into two main parts; in the first, we will discuss the importance of knowing learner’s mental model for both the teacher and the learner and the role of the creative teacher in dealing with it. Whereas in the second part, which will be practical, we will test second year students’ mental models regarding oral expression class using one of the measuring tools to come up in the end with some results and recommendations. الملخص في هذه الورقة نحاول تسليط الضوء على نموذج التمثيل العقلي للمتعلم و أهميته في فهم تمثيل المتعلم الفكري لتجربته التعليمية. فأحيانا النموذج الفكري الخاطئ يؤدي إلى ترجمات خاطئة تنبني عليه قرارات مستقبلية خاطئة ما يؤدي إلى عرقلة التعلم الفعال و الصحيح. و حتتى نتعامل مع النموذج الفكري للمتعلم على األستاذ أن يكون ذا مهارات إبداعية تسمح له بالتعامل مع النموذج الفكري للمتعلم من خالل محاولة فهم و تحليل المستوى المعرفي للمتعلم و إيجاد البدائل من أجل حل المشاكل التعليمية للمتعلم. و على ضوء هذا نقسم ورقتنا إلى جزئين مهمين. ففي األول نناقش أهمية معرفة النموذج الفكري للمتعلم لكال المعلم و المتعلم و الدور المهم لألستاذ المبدع في التعامل معه. و في الجزء الثاني و هو تطبيقي بحثنا فيه على النموذج أو التمثيل الفكري لطلبة السنة الثانية فيما يخص ماذة التعبير الشفهي بإستعمال أحد أدوات القباس المقترحة انخرج بعدها بنتائج مهمة و توصيات مستقبلية.
Keywords: Key words: mental model, creative teacher, effective learning, Kenneth Graik's theory, measuring the mental model. ا